Efeitos da pulverização foliar com silício na tolerância de Theobroma cacao L. (Malvaceae) ao défice hídrico - Zanetti, Leonardo Valandro (2013)
As in many Brazilian regions, the northern of Espírito Santo, a polo cocoa producer, has intense periods of drought that causes decline in agricultural production. Every farmer longs for the development of good quality and low cost technologies for increasing production, and it is in this context that arise the fertilization with silicon (Si), a technology little explored in Brazil and already shows promise in maintaining or increasing productivity in situations of drought stress. Therefore, the aim of this work was to check anatomic and physiological responses of a clone of cocoa (PH 16) subjected to water deficits cycle, after foliar feeding with silicon, to determine whether Si confers drought tolerance. The experiment was conducted in a greenhouse in a randomized block design with four replications in a 2 x 3 factorial, with two levels of irrigation, irrigated or non-irrigated, and three silicon doses: 0.0, 1.5 and 3.0 mg/mL, with a wettable powder of SiO2. After twenty days without irrigation, evaluations were performed in the 2nd or 3rd fully expanded leaf from the apex of the orthotropic axis.The results showedthat the phenol content was higher with SiO2 application independent of dose.The useof SiO2improved cell membranes stability in plants under water deficitsand the antioxidant activity of some enzymes including catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (POD) and polyphenoloxidase (PPO), and the use of 1.5 mg/ml was the best dose. The application of this dose favored the photochemical reactions, photosynthetic rate, water-use efficiency and carboxylation rateof the cocoa plants under water deficits. Stomatal density was not reduced in plants irrigated with the higher dose of Si. However, the application of Si did not affect the water content of the leaves under deficit, despite reducing leaf water potential. It is supposedthat themucilage has an important role in maintaining the water content of T. cacao leaves.The thickness of leaf tissues (epidermis, palisade and spongy parenchyma), as well as the photosynthetic pigment content and the content of silicon in the leaves also were not influenced by the different doses of silicon.Thus, it is suggested that the accumulation of Si on the leaves was beneficial, with the dose of 1.5 mg / mLbeingthe most efficient for the cocoa plant tolerance to water deficit.